Studies on Fusicladium Leaf Spot of Pongamia pinnata - , Jamaluddin; Dadwal, V. S.; Soni, K. K. (Indian Forester, 1981)
Fusicladium pongamae Syd. Caused severe foliage blight of Pongamia pinnata Pierre in nurseries. The symptoms, histopathology and pathogenicity of the organism were studied. There was heavy conidiation by the organism which germinated at appropriate humidity and temperature thereby infecting the healthy leaves. Sugars, organic acids and phenolics were observed chromotographically in healthy and the diseased leaves. The increase in the organic acid and phenolics was related with the mechanism of disease resistance during infection processes. Amongst the fungicides tried, bavistin, ziride and benlate were more effective in controlling the infection. Any of these fungicides may be sprayed at 0.2 per cent when the inoculum in the form of spores very less.